A Case of Reversible Cerebral Vasoconstriction Syndrome Triggered by High‐Dose Methotrexate in a Boy With Lymphoma. Issue 8 (15th April 2019) - Wang, Xiaona; Zhang, Yan; You, Hui; Zhu, Tienan; Zhou, Daobin
Abstract : Background: Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by thunderclap headaches and transient segmental cerebral arterial vasoconstriction. Many drugs have been identified as triggers of RCVS. However, RCVS induced by methotrexate (MTX), an antimetabolite agent, has never been reported. Case: We report the first case of a 17‐year‐old Chinese student with a thunderclap headache after administration of high‐dose methotrexate during the treatment of extranodal natural killer/T‐cell lymphoma. Brain magnetic resonance angiography showed segmental constriction of the right anterior cerebral artery A1 segment, combined with nonaneurysmal cortical subarachnoid hemorrhage and vasogenic brain edema in brain magnetic resonance imaging. Cerebral images became normal 6 weeks later. Discussion: MTX is associated with a variety of neurological toxicities, including aseptic meningitis, transverse myelopathy, acute and subacute encephalopathy, and leukoencephalopathy. However, this is the first report that MTX can trigger RCVS, although it is not a proof for causality. RCVS should be a differential diagnosis for a headache after MTX administration.